Investigation of the temporal and spatial dynamics of muscular action potentials through optically pumped magnetometers. (August 2021) - Broser, Philip J.; Marquetand, Justus; Middelmann, Thomas; Sometti, Davide; Braun, Christoph
Highlights: A robust technique for triggering a muscular action potential that can be recorded by MMG and needle EMG simultaneously. The correlation of the MMG signal with the needle EMG signal. A method for detecting the direction of the propagating muscular action potential. A method for correlating the magnetic field vectors with the pinnation angle of the examined muscle. Abstract: Aim: This study aims to simultaneously record the magnetic and electric components of the propagating muscular action potential. Method: A single-subject study of the monosynaptic stretch reflex of the musculus rectus femoris was performed; the magnetic field generated by the muscular activity was recorded in all three spatial directions by five optically pumped magnetometers. In addition, the electric field was recorded by four invasive fine-wire needle electrodes. The magnetic and electric fields were compared by modelling the muscular anatomy of the rectus femoris muscle and by simulating the corresponding magnetic field vectors. Results: The magnetomyography (MMG) signal can reliably be recorded following the stimulation of the monosynaptic stretch reflex. The MMG signal shows several phases of activity inside the muscle, the first of which is the propagating muscular action potential. As predicted by the finite wire model, the magnetic field vectors of the propagating muscular action potential are generated by the current flowing along the muscle fiber. Based on the magnetic field vectors, it was possible to reconstruct the pinnation angle of the muscle fibers. The later magnetic field components are linked to the activation of the contractile apparatus. Interpretation MMG allows to analyze the muscle physiology from the propagating muscular action potential to the initiation of the contractile apparatus. At the same time, this methods reveals information about muscle fiber direction and extend. With the development of high-resolution magnetic cameras, that are based on OPM technology, it will be possible to image the function and structure of the biomagnetic field of any skeletal muscle with high precision. This method could be used both, in clinical medicine and also in sports science.